The Role of Comparative Analysis in the Development of the Language and Literature of Different Countries (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the significant role of comparative analysis in the development of language and literature, focusing on the English and Uzbek languages as a case study. Comparative linguistics, by examining similarities and differences between languages, illuminates historical relationships, influences, and evolutionary paths. This study investigates how comparative analysis has contributed to understanding the historical development of both English and Uzbek, including the impact of language contact, borrowing, and internal evolution. Furthermore, it analyzes how comparative literary studies, by comparing literary works, themes, and genres across cultures, enriches our understanding of cultural exchange, shared human experiences, and unique artistic expressions. The article argues that comparative analysis is crucial for fostering cross-cultural understanding, promoting language preservation, and advancing both linguistic and literary scholarship. It concludes by highlighting the ongoing relevance of comparative studies in a globalized world, emphasizing its potential to unlock deeper insights into the interconnectedness of human language and culture.